The Face Of Islam After The 2019 Presidential Election: Democracy And The Challenge Of Dialogue - Muhammad Radya Yudantiasa (Jurnal Dialog, 2020)
This article examines the problems of intra/interreligious dialogue that occurred after the 2019 presidential election. The focus of this study is to analyse the impact of Islamic populism on the sustainability of dialogue in Indonesia. The trend of Islamic populism is basically narrative and analytic of Indonesian political studies. The political contestation has an impact on the intra/inter-religious dialogue problems or even transcending ethnic and group boundaries. This situation requires intense dialogue among scholars, activists, elites, religious leaders and society members. This research is a library research using descriptive-analysis method. The main theory in this research is agonistic theory. This theory sees the conflict from more positive ways. This article argues that the discourse and the narration of moderate Islam needs to be brought into public sphere. Hence, the peaceful characters of Islam and tolerant Islam become the dominant colors of Islam in the public sphere. Artikel ini mengungkap kembali problematika tentang dialog pasca pemilihan presiden 2019. Fokus dari artikel ini adalah untuk menganalisis pengaruh dari populisme Islam terhadap keberlanjutan dialog di Indonesia. Tren dari populisme Islam pada dasarnya merupakan sebuah narasi dan analisis yang banyak dikaji dalam lingkup studi politik di Indonesia. Peristiwa kontestasi politik yang terjadi di dalam pemilihan presiden 2019 menunjukkan adanya permasalahan terhadap dialog dalam/antar agama dan bahkan melampaui batas-batas etnik maupun kelompok agama. Situasi ini meniscayakan para aktor-aktor dialog dari kalangan akademisi, aktivis, elit politik, pemuka agama, dan masyarakat untuk terlibat dalam kontestasi ini. Penelitian ini merupakan studi kepustakaan (library research) dengan menggunakan metode deskriptif-analisis. Teori utama yang digunakan dalam artikel ini adalah teori agonistik (agonistic theory). Teori ini berfungsi untuk melihat konflik dalam sudut pandang yang positif. Artikel ini menyimpulkan bahwa klaim tentang wacana dan narasi Islam yang moderat harus muncul untuk dikontestasikan dalam ruang publik. Dengan demikian, wajah asli Islam yang damai, toleran dan rahmatan lil-‘alamin akan menjadi wajah yang dominan dalam ruang publik.